Sprzątanie w wielkim mieście. Polskie imigrantki na nowojorskim rynku pracy. Część 1 - Anna Sosnowska (University of Warsaw, Centre of Migration Research (CMR), 2014)
– The text, consisting of two parts, presents conclusions from the exploratory research on the Polish female niche on the New York City immigrant labor market - cleaning. Part 1 points out the crucial character of the working class niches on the Western labor markets for the image of Poland and for Polish identity itself. Critically referring to Waldinger's theory of ethnic queue, ethnic niche and immigrant and ethnic enterprise as well as to historical research on transformation of the domestic workers' social status, the study attempts at explaining why Polish immigrants have not established a niche in the sector of Manhattan's office cleaning. The circumstances of the change in the ethnic queue that were not identified by Waldinger are pointed out and discussed.
Keywords: 330; labor migrants; New York City (United States); cleaners; ethnic niche; ethnic queue